Measurements of Branching Fractions and Time-dependent CP Violating Asymmetries in $B^{0} → D^{(*)±}D^{\mp}$ Decays - Collaboration, B; Röhrken, M; Adachi, I; Aihara, H; Asner, D; Aulchenko, V; Aushev, T; Bakich, A; Barrett, M; Belous, K; Bhardwaj, V; Bhuyan, B; et al. (2012)
We report measurements of branching fractions and time-dependent CP asymmetries in $B^{0} → D^{+}D^{-}$ and $B^{0} → D^{*±}D^{\mp}$ decays using a data sample that contains $(772 ± 11)× 10^6 B\bar{B}$ pairs collected at the $Υ(4S)$ resonance with the Belle detector at the KEKB asymmetric-energy $e^+ e^-$ collider. We determine the branching fractions to be $\mathcal{B}(B^{0} → D^{+}D^{-})=(2.12 ± 0.16 ± 0.18)× 10^{-4}$ and $\mathcal{B}(B^{0} → D^{*±}D^{\mp}=(6.14 ± 0.29 ± 0.50)× 10^{-4}$. We measure CP asymmetry parameters $\mathcal{S}_{D^{+}D^{-}} = -1.06_{-0.14}^{+0.21} ± 0.08$ and $\mathcal{C}_{D^{+}D^{-}} = -0.43 ± 0.16 ± 0.05$ in $B^{0} → D^{+}D^{-}$ and $\mathcal{A}_{D^{*}D} = +0.06 ± 0.05 ± 0.02$, $\mathcal{S}_{D^{*}D} = -0.78 ± 0.15 ± 0.05$, $\mathcal{C}_{D^{*}D} = -0.01 ± 0.11 ± 0.04$, $Δ\mathcal{S}_{D^{*}D} = -0.13 ± 0.15 ± 0.04$ and $Δ\mathcal{C}_{D^{*}D} = +0.12 ± 0.11 ± 0.03$ in $B^{0} → D^{*±}D^{\mp}$, where the first uncertainty is statistical and the second is systematic. We exclude the conservation of CP symmetry in both decays at equal to or greater than $4σ$ significance.